APLIKASI PENJUALAN ANEKA OLAHAN IKAN BERBASIS WEB MENGGUNAKAN METODE MARKETPLACE - Iyan Sunandar; Sri Nuryani; Fachmi Ramdani (INFOKOM (Informatika & Komputer), 2025)
Marketing activities are a form of assessment of the success of marketing activities carried out comprehensively by a company or organization. Thus, marketing activities can be viewed as a concept to measure the extent to which results are achieved by the company's products. This study aims to uncover the forms and processes of marketing activities at the Various Fish Processing Gallery in Ambulu Village, Losari District. This study used a qualitative approach through literature studies, interviews, and field studies to observe the processed fish products produced by the gallery. The results showed that marketing activities were carried out by prioritizing the authentic taste of the product and the quality of its packaging. Marketing also utilized a web-based sales application with a marketplace method. The processed fish products from this gallery have a distinctive taste that is a main selling point. However, promotional activities are still limited to the Ciayumajakuning area. Nevertheless, the use of a web-based application with a marketplace method is expected to increase sales results compared to before. In terms of pricing, the Various Fish Processing Gallery in Ambulu Village applies competitive prices and is able to compete in the market